ANALISIS KELAYAKAN POTENSI EKOWISATA DI KAWASAN PENYANGGA TAHURA SULTAN SYARIF HASYIM KELURAHAN MINAS JAYA - Nainggolan, Yan; Suhesti, Eni; Tri Ratnaningsih, Ambar (Fakultas Kehutanan Universitas Lancang Kuning, 2019)
This study aims to determine the potential for ecotourism and the feasibility of the potential of ecotourism in the Tahura buffer zone of Sultan Syarif Hasyim, Minas Jaya Village. This research was conducted by means of a survey to obtain data through interviews and questionnaires in which the sample of respondents was taken by accidental sampling. From the results of research that has been done, this area deserves to be developed into a tourist area because it is found the potential of ecotourism objects in the form of a wealth of natural resources such as flora and fauna, the beauty of the lake and its landscape, as well as many natural tourism activities that can be carried out. The Tahura Buffer Area of ​​Sultan Syarif Hasyim, Minas Jaya Village, is feasible to be developed with the level of eligibility of each class with a score of each class, namely 846 attractiveness, 144 accommodations, 300 infrastructure. While for accessibility class it cannot be said to be feasible with a score of 455.